PENGARUH SELF EFFICACY DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MINAT BERWIRAUSAHA SISWA - Cessa Vierintino; Yopi Nisa Febianti; Endang Herawan (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2023)
Efforts to increase awareness of entrepreneurship, including by growing interest in entrepreneurship. With the interest that exists in students, students will be encouraged to study knowledge related to entrepreneurship more seriously. The purpose of this study was to determine the effect of self-efficacy and socio-economic status of parents on the interest in entrepreneurship in class XII IPS students at MAN 1 Cirebon. This research method uses quantitative research, Data collection using questionnaires, interviews and documentation. Data analysis technique using the classical assumption test and hypothesis testing.. The research results show that self-efficacy has a positive and significant effect on the interest in entrepreneurship, the socio-economic status of parents has a positive and significant effect on students'interest in entrepreneurship, and the self-efficacy and socio-economic status of parents simultaneously have a positive and significant effect on interest in entrepreneurship class XII students at MAN 1 Cirebon.